Climate, Food Systems, and Diets Worksop in Busia, Kenya - Sarku, Rebecca; Moturi, Frank; Nabwire, Florence; Styles, Robin; Whitfield, Stephen (CGIAR System Organization, 2024)
The aim of this workshop was to introduce the ClimBeR research to stakeholders in the Busia County, discuss how the Integrated Future Estimator for Emissions and Diets (iFEED) was being utilized to model various pathways, particularly those associated with crop diversification and investments in irrigation under climate change contexts.